Foot Bath with warm water for hypertension therapy : A narrative review - Bietris Warisyu; Elly Nurrachmah; Riri Maria (Universitas Muhammadiyah Surakarta, 2023)
Soak feet with warm water is a combined therapy method of thermotherapy and hydrotherapy that works to release istamine and bradykinin. The release of istamine and bradykinin causes vasodilation of blood vessels. The purpose of the study: to identify the effect of soaking the feet with warm water on lowering blood pressure. Method:This research is a quantitative research with a systematic review method. The research design used was Randomized Controlled Trials (RCT) with 9 studies.Results:Obtained from 9 studies the average p-value <0.05. p-value of diastolic blood pressure was 0.00 and p-value of systolic blood pressure was 0.00. Conclusion:Warm water therapy can be put incomplementary therapy groupcare for hypertensive patients. However, the temperature and duration of soaking the feet with warm water must be considered in order to avoid hypotension or low blood pressure